Peningkatan hasil belajar matematika melalui model Problem Based Learning (PBL) berbantuan card sort siswa kelas lima - Arini Mayang Fauni (Math Didactic: Jurnal Pendidikan Matematika, 2019)
The aim of the research is to describe the increasing Mathematic scores for students grade five at SDN Kutowinangun 04 Term one education year 2018atau2019 through Problem Based Learning (PBL) with Card Sort strategy. The research is classroom action research which consisted of two cycles, there would be three stages in every cycle: planning, action and observation, reflection and evaluation. The data gained in formed of Mathematic tests in the end of 1st and 2nd cyle. Data analysis technique used was comparative and critical techniques. The result of the research showed that there was a significant enhancement of Mathematic scores. The enhancement could be seen from its indicators as follow: 1) the students were enthusiastic to ask before action 10,34%, 1st cycle 20,68%, and 2nd cycle 34, 48%, 2) the students were enthusiastic to answer the questions ask before action 13,79%, 1st cycle 27,59%, and 2nd cycle 55,17%, 3) the students were eager to do the exercises in front of the classroom before action 17,24%, 1st cycle 34,48%, and 2nd cycle 65,52%. The enhancement of students’ Mathematic scores could be seen from the scores which achieved Minimum Criteria of Mastery Learning (KKM) before action 20,68%, 1st cycle 44,82%, and 2nd cycle 89,65%. Based on the description above, it could be concluded that the implication of Problem Based Learning with Card Sort Strategy in learning Mathematic could increase Mathematic scores.